Legal regulation of The crime of the transfer of human organs from the dead to the livin - حسين, الاء ناصر; هاشم, عمار سليم (Journal of Legal Sciences, 2019)
Human organ transport and transplants are a type of medical work and are therefore generally subject to the same rules governing medical work. Ensure that such practices do not deviate from their specific legal framework in such a way as to ensure the preservation of the human body and respect for its dignity.The Iraqi legislator in the Law of Transplantation and Prevention of Trading in Human Organisms No. (11) of 2016 prohibited the transfer of organ or human tissue from the dead to the living body and stipulated that the transfer of organs from the dead should require the consent of the Deceased before his death under a will or approval He inherited it.The regulation of transplantation and transplantation of human organs in this way does not preclude the fact that these processes are still and will remain at the exclusion angle at least from the criminal point of view. Therefore, these operations must be organized with utmost care and precision, so as not to depart from the exception. To be between the two circles are the circle of exception and the Criminalization Chamber, if these operations came out of the exception, they will inevitably enter the circle of criminalization, the violation of any condition of the pornographic transfers and transplantation of human organs, these operations come out of the exclusion Chamber and result in the crime of transfer and button Members of the human and then impose sanctions and precautionary measures against both. Contravenes the provisions of the Human Organ Transplantation Act.